An Examination of The Aflatoxin Concentration of Corn and How It Affects Laying Hen Performance on Farms in North Lombok Regency - Dwi Kusuma Purnamasari; I.K.G. Wiryawan; Maslami, Vebera; Noersidiq, Azhary; Fahrullah, Fahrullah; Erwan, Erwan; Syamsuhaidi, Syamsuhaidi; Sumiati, Sumiati; Rohima, BQ. Nahya (Jurnal Biologi Tropis, 2024)
The mold Aspergillus flavus produces a metabolite molecule called aflatoxin. Aflatoxin chemicals can have harmful effects on both humans and livestock when they are present in feed ingredients. Aspergillus flavus frequently grows on corn, one of the feed ingredients. Examining the amount of aflatoxin contamination in corn in North Lombok Regency and how it affects laying hen performance was the goal of this study. Random sampling was done from each subdistrict, and descriptive analysis was done on the collected data. According to the study's findings, aflatoxin compounds, which have a range of 87.99–132.38, were found in 50% of corn. Aflatoxin concentration in feed surpasses the 60 ppm SNI guideline by 33.33%.  Performance is impacted by aflatoxin compounds in maize; specifically, 50% of feed intake, 50% of egg weight, and 100% of noncompliance with SNI and corporate criteria are not met. The results of this study suggest that aflatoxin levels in diet have an impact on laying hens' declining performance.